Early Breastfeeding Initiation And Exclusive Breastfeeding Impact On Growth Of Baby From One To Six Months Of Age - Lisa Pangemanan; Benedictus Triagung Ruddy Prabantoro; Susan Susan (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Early breastfeeding initiation is provision of mother’s breast milk to infant within one hour of birth. It is used to promote breastfeeding. Breastfeeding has many health benefit for infant because of its important nutritional contribution. Studies in developing countries has found that frequent breastfeeding is associated with greater linear growth. However, rate of exclusive breastfeeding is still low in many countries, among others, Indonesia (